Perceived Preparedness of Healthcare Workers to Cope with COVID-19 Pandemic in Hail Region Hospitals, Kingdom of Saudi Arabia: A Cross-Sectional Study - Alshammari, Farhan; Rondilla, Evalynn; Asharari, Abdalkarem; Alshammari, Fahad (UI Scholars Hub, 2021)
Background: All hospitals must have emergency plans because they play a crucial role in providing critical care. This study assesses the perceived hospital preparedness of healthcare workforces to cope with the COVID-19 pandemic regarding their demographic characteristics. Methods: This study utilized a descriptive, cross-sectional design to investigate the preparedness of hospital and healthcare workers in the city of Hail, Saudi Arabia. A convenience and snowball sampling method was used. A total of 330 healthcare workers participated in the study, which utilized a Google Form survey and was adapted from the Centers for Disease Control and Prevention (CDC). Descriptive statistics, t-test, one-way ANOVA, and Kruskal-Wallis were used to analyze the data. Data collection was conducted in July and August 2020. Results: Overall, hospital employees agreed that they and their hospital were prepared for COVID-19 (2.98). No significant difference (p > 0.362) was found in the perception of male and female employees. However, hospital preparedness significantly differed by profession (p < 0.020) and educational attainment (p < 0.030); the post hoc test showed that COVID-19 preparedness was high for respondents with higher educational attainment, years of experience (p < 0.003), and the number of training sessions attended (p < 0.003). Conclusions: The healthcare workforce is prepared to combat COVID-19. Of the demographic profiles of the healthcare workers, only sex was not a factor in preparedness. Profession, educational attainment, years of experience, and the number of related training sessions were all determinants of the healthcare workers’ preparedness. These demographic characteristics can serve as factors in training and retraining the staff in battling COVID-19.